Pemberdayaan Masyarakat melalui Pengenalan pada Aplikasi PrimaKu di Posyandu Bukit Tinggi Harapan 3 Desa Dete - Herni Hasifah; Iga Maliga; Ana Lestari; Rafi’ah Rafi’ah (Lembaga Pengembangan Kinerja Dosen, 2025)
Growth and development disorders in children can have a significant impact on their overall well-being, manifesting in various forms such as delays in fine and gross motor development, speech and hearing impairments, and even intellectual disabilities. Early detection of these issues is crucial for initiating timely interventions that can improve the child's quality of life. With technological advancements, various applications have emerged, providing an accessible means for parents to independently monitor their children's growth and development. One such tool is the PrimaKu application, which enables parents to track and assess their children's growth and developmental milestones at home. The aim of this service is to empower parents by enhancing their understanding and knowledge regarding the monitoring of their children's development, thereby promoting early detection of potential growth issues. The approach utilized in this service involves providing counseling on child growth and development, alongside demonstrations on how to use the PrimaKu application effectively. A survey conducted during the service activities revealed that the majority of participants (70%) had limited knowledge about child development, while 20% demonstrated adequate knowledge, and only 10% exhibited good knowledge. These findings indicate a significant gap in parents' awareness of child development. As a result, it is recommended that ongoing educational efforts be made at posyandu centers to further educate parents about child development. Introducing the PrimaKu application at these centers could also facilitate better tracking of children's growth and developmental progress, as the app serves as a useful tool for both parents and healthcare providers in ensuring that children meet important developmental milestones. The continuous integration of technology, such as the PrimaKu app, into child healthcare services could significantly contribute to improving early intervention practices and overall child development outcomes.